2020
DOI: 10.1111/tmi.13393
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between mental health conditions and hearing loss in low‐ and middle‐income countries

Abstract: objective Hearing loss can have far-reaching effects on social, emotional and cognitive development, but few studies have addressed the link with mental health conditions. We conducted a systematic review of the association between hearing loss and mental health conditions in low-and middle-income countries (LMICs).methods We searched six electronic databases using predetermined criteria to retrieve original research reporting mental health in people with hearing loss. We considered quantitative studies measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 59 publications
2
1
0
Order By: Relevance
“…Our findings are consistent with the previous literature about the association of HL and depression symptoms 41 . A systematic review investigating the relationship of HL and mental health conditions in LMICs included 12 studies and provided evidence that hearing loss was associated with statistically greater odds of depression 42 . Compared with previous studies, our analyses offered compelling and robust evidence of an association between HL and depression symptoms according to the objective measures of functional hearing.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are consistent with the previous literature about the association of HL and depression symptoms 41 . A systematic review investigating the relationship of HL and mental health conditions in LMICs included 12 studies and provided evidence that hearing loss was associated with statistically greater odds of depression 42 . Compared with previous studies, our analyses offered compelling and robust evidence of an association between HL and depression symptoms according to the objective measures of functional hearing.…”
Section: Discussionsupporting
confidence: 90%
“…In relation to personal factors, meeting the criteria for any RCADS disorder was significantly associated with older age (11–19 years, OR = 2.05), special educational needs (OR = 4.54) and poor health (OR = 4.87). This reflects findings from the extant literature which consistently identifies higher rates of rates of mental health disorders amongst older children ( Kessler et al, 2007 ), as well as associations between child mental health problems, physical health, chronic illness and disabilities ( Pinquart & Shen, 2011a ; 2011b ; Augestad, 2017 ; Jiang et al, 2020 ). Likewise, the MHCYPS (2017) England found that older children, those with special educational needs and those with poorer health, had higher rates of emotional disorders than those without ( Vizard et al, 2018 ).…”
Section: Discussionsupporting
confidence: 68%
“…Kvam and her colleagues reported that whereas 1% of the respondents in general population were anxious, the percentage among the deaf respondents was 10% [ 26 ]. Defect in language skills due to the hearing loss can affect the communication, and consequently can have a devastating effect on emotional and psychosocial functioning [ 27 ].…”
Section: Introductionmentioning
confidence: 99%